Kanamycin complexation with cellulose acetate sulphate: a promissing way from injectable to oral form of antibiotic - Savitskaya, Tatsiana A.; Shakhno, Ekaterina A.; Bosko, Ivan P.; Matulis, Vadim E.; Melekhovets, Natallia A.; Grinshpan, Dmitry D.; Ivashkevich, Oleg A. (Journal of the Belarusian State University. Chemistry, 2021)
Water-insoluble polyelectrolyte complexes of cellulose acetate sulphate in the form of sodium salt (Na-CAS) and aminoglycoside antibiotic (AB) kanamycin (KAN) were obtained by mixing of the components aqueous solutions. The composition of the complexes was determined in accordance with the medium pH and mixing order. The increase of Na‑CAS cellobiose units per mole of AB has been shown to correlate with the decrease of pH value. The complex formation was studied by Fourier transform infrared spectroscopy, thermal analysis, X-ray analysis, laser diffraction, motion trajectory of nanoparticles analysis and scanning electron microscopy. Quantum-chemical study of the relative stability of the protonated forms of KAN in aqueous solution was performed to determine the preferred protonation sites of KAN molecule. The pKa values of KAN were calculated by means of isodesmic reactions method. The structures and binding energy for the KAN dimer and the KAN – CAS complex were also investigated by quantum-chemical methods. Na‑CAS – KAN complex itself and immobilised on the activated carbon was shown to demonstrate in vitro two times antibacterial activity of the standard (injectable) form of KAN against Mycobacterium tuberculosis. It can be recommended for in vivo clinical trials as a new form of aminoglycoside AB for oral administration.